Degree of reliability of the assessment of the Bolton analysis in three-dimensional virtual models versus plaster models. A review - Loma Salcedo, Humberto (2023)
Introduction: Bolton analysis is used to determine anomalies with respect to the dental mass, for diagnosis and treatment planning purposes, the possibility of using a digital method was introduced and tested to measure the size of the mesiodistal tooth. In this way, digital dental technology has made digital study models become popular in orthodontics. Objective: to evaluate the degree of reliability of the evaluation of the Bolton analysis in three-dimensional virtual models versus plaster models through a review of the literature. Materials and methods: A search was carried out in the primary databases of the international scientific literature on health sciences: Medline, through PubMed, SciELO, Lilacs, and Embase. Review articles published between the year 2000 and October 2021 were included. Results: The desktop scanner was the best option for digitizing dental models, but this does not detract from CBCT and intraoral laser scanners, which are still an option. Reasonable validity for digitizing 3D models with results within the "clinically acceptable" range was found. Conclusions: 3D digital models generated with intraoral and extraoral scanners are reliable and accurate compared to conventional impressions and save time, in most cases statistically significant differences were found, but of little clinical relevance.